DNA-assisted upconversion nanoplatform for imaging-guided synergistic therapy and laser-switchable drug detoxification. (August 2017) - Li, Luoyuan; Hao, Panlong; Wei, Peng; Fu, Limin; Ai, Xicheng; Zhang, Jianping; Zhou, Jing
Abstract: The side effects of chemotherapy bring significant physical and psychological suffering to patients. To solve this urgent medical problem, Yb 3+ and Er 3+ co-doped NaLuF4 upconversion nanoparticles (UCNPs) were constructed for upconversion luminescence (UCL)-labeled diagnosis under 980 nm laser irradiation. The UCNPs were then modified layer by layer with polypyrrole and a special programming DNA segment as photothermal conversion agents and controllable drug carriers, respectively. The nanoplatform was successfully used for imaging-guided synergistic therapy (photothermal therapy and chemotherapy) at a safe power density (300 mW cm −2 ), and DNA-assisted detoxification at lower temperature in cancer cells when the laser off. The synergistic therapy of the nanoplatform achieved a higher therapeutic index (∼85%) than chemotherapy only (∼44%) and photothermal therapy only (∼25%) in vitro . In vivo experiments also suggested that the nanoplatform had a higher therapeutic effect and lower side effects. The toxicity study was also evaluated, indicating the nanoplatform is low toxic to living system. This multifunctional upconversion nanoplatform provided an innovative method for imaging-guided photothermal-chemotherapy and laser-switchable drug detoxification.